2012
DOI: 10.1371/journal.pone.0038776
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transfer of Human VEGF165 and HGF Genes Renders Potent Angiogenic Effect in Ischemic Skeletal Muscle

Abstract: Increased interest in development of combined gene therapy emerges from results of recent clinical trials that indicate good safety yet unexpected low efficacy of “single-gene” administration. Multiple studies showed that vascular endothelial growth factor 165 aminoacid form (VEGF165) and hepatocyte growth factor (HGF) can be used for induction of angiogenesis in ischemic myocardium and skeletal muscle. Gene transfer system composed of a novel cytomegalovirus-based (CMV) plasmid vector and codon-optimized huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 34 publications
5
39
0
1
Order By: Relevance
“…4 days after treatment mice were sacrificed by anesthetic overdose, tibial anterior muscles were extracted and homogenized in 450 ml of buffer (0.5 M NaCl, 20 mM Tris and 1 mM EDTA) [10]; the homogenates were studied for the presence of muPA using muPA ELISA kit (''Cell Sciences'', cat #CSI19903A) according to the manufacturer instructions. Injection of pVax1 at the same dose was used as a control.…”
Section: Mupa Expression Analysismentioning
confidence: 99%
“…4 days after treatment mice were sacrificed by anesthetic overdose, tibial anterior muscles were extracted and homogenized in 450 ml of buffer (0.5 M NaCl, 20 mM Tris and 1 mM EDTA) [10]; the homogenates were studied for the presence of muPA using muPA ELISA kit (''Cell Sciences'', cat #CSI19903A) according to the manufacturer instructions. Injection of pVax1 at the same dose was used as a control.…”
Section: Mupa Expression Analysismentioning
confidence: 99%
“…This puts the basis for combined gene therapy to treat ischemia with higher eicacy and it has been supported by experimental indings using VEGF165 combined with another pro-angiogenic growth factor: bFGF [71], PDGF [72], angiopoietin-1 [73], or Stromal cell-derived factor-1α (SDF-1α) [74]. Our previous experience in mouse hind limb ischemia model showed that combination of VEGF165 and uPA [75] or HGF [76] induced angiogenic response more efectively than each factor alone or allowed to reduce pDNA dose for combined delivery [75]. A crucial transcription factor in angiogenesis, HIF-1α, was also used for combined gene therapy with VEGF165 showing good results in animal model [77] as well as bFGF + heme oxygenase-1 (HO-1) [78].…”
Section: Gene Therapy For Angiogenesismentioning
confidence: 79%
“…М.В. Ломоносова, на моделях ишемии задних конечно-стей и инфаркта миокарда у мышей выявлены аддитив-ный ангио-и артериогенный эффекты VEGF165 и HGF, способствовавшие максимальному восстановлению пер-фузии пораженных тканей (до 70%) [44]. Помимо иссле-дований вышеуказанных конструкций авторы работают над созданием генномодицированных клеток, которые, возможно, будут способствовать индукции ангиогенеза и реперфузии ишемизированных тканей [61].…”
Section: кардиология и сердечно-сосудистая хирургия 6 2015unclassified